2004
DOI: 10.4049/jimmunol.172.7.4151
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Intraepithelial Lymphocyte γδ-T Cell-Derived Keratinocyte Growth Factor Modulates Epithelial Growth in the Mouse

Abstract: Keratinocyte growth factor (KGF) promotes intestinal epithelial growth. To understand the relevance of intraepithelial lymphocyte (IEL)-derived KGF expression on epithelial growth, we used a mouse model of villus atrophy by the administration of total parenteral nutrition, and a model of villus hypertrophy by the creation of a short bowel syndrome. KGF expression was confined to γδ-ΤCR+ IELs. IEL-derived KGF expression was highest in the crypts, somewhat less in the lower portion of villi, and markedly lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
92
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(101 citation statements)
references
References 50 publications
(64 reference statements)
6
92
0
2
Order By: Relevance
“…The Wnt-β-catenin signalling pathway has a wellcharacterized role in T and B cell development (43,44) and is necessary for haematopoietic maturation (45 Min/+ mice with intact γδ IEL populations but lacking αβ IELs had significantly fewer tumours than mice that were deficient in γδ IELs. These findings also reinforce the concept of αβ and γδ IELs performing non-overlapping roles within the intestinal mucosa, with αβ IELs being important for immunity (49,50) and γδ T-cells contributing to epithelial homeostasis (51)(52)(53). Expression of NK-like molecules on non-MHC restricted γδ T-cells including NKG2D which can recognise ligands on stressed and transformed epithelial cells (27,28) is consistent with them being better equipped than αβ IELs to influence intestinal epithelial homeostasis.…”
Section: Discussionsupporting
confidence: 67%
“…The Wnt-β-catenin signalling pathway has a wellcharacterized role in T and B cell development (43,44) and is necessary for haematopoietic maturation (45 Min/+ mice with intact γδ IEL populations but lacking αβ IELs had significantly fewer tumours than mice that were deficient in γδ IELs. These findings also reinforce the concept of αβ and γδ IELs performing non-overlapping roles within the intestinal mucosa, with αβ IELs being important for immunity (49,50) and γδ T-cells contributing to epithelial homeostasis (51)(52)(53). Expression of NK-like molecules on non-MHC restricted γδ T-cells including NKG2D which can recognise ligands on stressed and transformed epithelial cells (27,28) is consistent with them being better equipped than αβ IELs to influence intestinal epithelial homeostasis.…”
Section: Discussionsupporting
confidence: 67%
“…Intestinal adaptation after massive SBR is a complex process involving numerous nutritive and non-nutritive factors that lead to cellular hyperplasia and result in compensatory increases in villus height and crypt depth (1,5,18). We set up our studies at 7 days post-resection because it has been shown that in rodents by this time-point the majority of post-resectional intestinal morphologic changes have been achieved (9).…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have demonstrated that crypt cell apoptosis progresses quite differently compared with apoptosis along the villi. It should be emphasized that many trophic factors act differentially along the crypt-villus axis in accordance with differential expressions of their receptor (13,14). In a recent study, we have shown that the TGF-␣ inhibits cell apoptosis in crypts, but it enhances cell apoptosis in villus tips and correlates with different epidermalgrowth factor receptor expressions along the villus-crypt axis (15).…”
Section: Discussionmentioning
confidence: 99%